2006
DOI: 10.1177/0272989x06290486
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Decision Aid for Women at Increased Risk of Ovarian Cancer

Abstract: This form of educational material is successful in increasing knowledge about risk management options and in reducing decisional conflict in the shorter term. The decision aid is an effective and acceptable strategy for patient education to facilitate an inclusive and informed decision-making process about managing ovarian cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Although this phenomenon has been identified in previous studies in the familial cancer setting, the discrepancy between the general and clinical population appears to be narrowing [39]. For example, earlier Australian data reported post-school qualifications in over 70% of women attending familial cancer clinics [48,49], suggesting that the numbers of women with lower educational levels is increasing in familial cancer clinics.…”
Section: Limitationsmentioning
confidence: 83%
“…Although this phenomenon has been identified in previous studies in the familial cancer setting, the discrepancy between the general and clinical population appears to be narrowing [39]. For example, earlier Australian data reported post-school qualifications in over 70% of women attending familial cancer clinics [48,49], suggesting that the numbers of women with lower educational levels is increasing in familial cancer clinics.…”
Section: Limitationsmentioning
confidence: 83%
“…[54] Randomized trials have shown the impact of decision support interventions on reduced DC, most often measured by the total score of the DCS. Despite the wide use of DC as an outcome in such trials, few studies have conducted analyses adjusting for baseline measures and demographics.…”
Section: Discussionmentioning
confidence: 99%
“…No significant effects were found after use of decision aids for coronary revascularization, 55 risk reducing mastectomy, 56 prophylactic oophorectomy, 57 or gynecologic procedures for menorrhagia. 58,59 …”
Section: Resultsmentioning
confidence: 90%